Ethnic fractionalization, natural resources and armed conflict. (September 2014) - Wegenast, Tim C.; Basedau, Matthias
Thus far, researchers working on ethnicity and resources as determinants of civil conflict have operated largely independently of each other. While there is plenty of evidence that natural resources may spur armed conflict, empirical evidence for the nexus between ethnic fractionalization and conflict remains inconclusive. Some authors conclude that ethnically fractionalized societies are actually spared from intrastate violence. Others find either a positive relationship or none at all between ethnic fragmentation and internal conflict. In this context, this paper serves two purposes: first, it shows that salience-based fractionalization indices are associated with a higher risk of ethnic conflict onset; second, it finds evidence that oil further increases the conflict potential within fractionalized countries. The combination of oil and a shared identity seems to help overcome the collective action problems associated with rebellion, by providing recruitment pools, strong motives and the necessary financial means for insurgency. Employing logit models for pooled time-series cross-sectional data, our quantitative analysis shows that various ethnic fractionalization indicators are robustly linked to a substantially increased risk of ethnic armed conflict onset in a subset of oil-abundant countries.